Explaining Caste Differences in Private School Attendance. Issue 4 (22nd January 2017) - Azam, Mehtabul
Abstract: Using a nationally representative education survey, we explore caste differences in private school attendance in India. We find lower private school attendance among the disadvantaged castes—Scheduled Castes (SCs), Scheduled Tribes (STs) and Other Backward Castes (OBCs)—when compared with the non‐disadvantaged group (non‐SC/ST/OBC). Controlling for geographical location, household and individual level factors reduces the gaps in private school attendance considerably; however, the gaps remain quite large. We find that variation in parental education and household consumption expenditure explains a significant proportion of the observed gaps. For ST students, geographical location remains important in explaining the gap in private school attendance.